(untitled) (BioLaw Journal - Rivista di BioDiritto, 2023)
The essay explores the use of artificial intelligence as a tool for content moderation by social media platforms and how it poses risks to the freedom of expression of LGBTQ+ individuals, perpetuating online the marginalization experienced by queer individuals offline. The EU’s Digital Services Act (DSA) regulation attempts to address this issue by balancing the need for content moderation with safeguards to freedom of expression. However, in order to mitigate the risks to the queer community’s freedom of expression, a regulatory approach must include transparency obligations on platforms that use algorithmic content moderation, but also avoid incentivizing social media to adopt a more aggressive and generalized moderation approach to elude the risk of being sanctioned, generating the so-called ‘better safe than sorry’ effect.